Performance Evaluation of Construction Project in Erbil City by adopting Site Layout planning - Haval M. Selki; Ahmet Oztas; Omed Dewary; Ayman A. Ahmed (Polytechnic Journal)
In general, construction site management is planning, organizing, leading, directing, monitoring, and controlling overall construction activities, during the implementation phase, one of the key elements of construction site management is site layout planning, which is identifying, sizing, and placing temporary facilities within construction boundaries. It has got enormous influence on project parameters. The main aim of this study is to investigate Erbil’s project’s site layout performance. The study was carried out in Erbil, 16 projects have selected for assessment. From the result, it was found that these projects suffer from poor site layout planning, as there was a poor plan for construction facilities, the location of these facilities was wrong, almost, all projects have neglected safety-related issues and much more factors which have been discussed in the analysis section. As a solution, the researcher believes that the current site layout design of projects need immediate improvement, planning should be considered as priority for every single temporary facility during construction; safety basic should be implemented, including wearing PPE; labor accommodation should be improved; sanitation of the workforce should be good; and many other site layout elements should be developed.